Evaluation of a New Maintenance Concept for the Preservation of Highways - Rommert Dekker; Raymond Ph. Plasmeijer; Jan H. Swart (Tinbergen Institute, 1997)
Asphalt roads are gradually deteriorating over time and need road mending to remain in a good state. Inspections are performed to obtain information about the current state of the road; when the damage achieves the established standards, the road is repaired through a maintenance action that is considered as most cost-effective. Because of economies of scale it is to a certain extent economical to limit the number of maintenance services by integrating neighboring segments into a homogeneous section which is completely repaired. In this report we consider the question whether it is economically justified to adopt a maintenance concept in which the road is occasionally regenerated from junction to junction with a distance of several kilometers. The big advantage of junction-to-junction maintenance is that it can be done within special road barrier constructions which reduce the road capacity only slightly, so that the road can be maintained 24 hours a day.
Keywords: 330; road maintenance; preservation of highways; junction to junction regeneration; pilot-study; traffic congestion; Straßenbau; Instandhaltung; Theorie